1993
DOI: 10.1071/ar9931799
|View full text |Cite
|
Sign up to set email alerts
|

Application of cytokinins to flowers to increase pod set in Lupinus angustifolius L

Abstract: Exogenous application of a 2 mol m-3 buffered solution of N6 benzylaminopurine (BAP) to flowers on the main stem inflorescence of Lupinus angustifolius L, cv. Danja profoundly altered reproductive development by reducing post-anthesis abscission of flowers and small pods. The same effect of BAP was recorded for a mutant (abs-) of cv. Danja, in which organ abscission was completely absent, indicating that localized application of cytokinin enhanced reproductive development rather than reduced pedicel abscission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…In tobacco, TP12 is most strongly expressed just prior to, and coinciding with, full flower opening and pollen release (Drews et al 1992). The earlier study (Atkins and Pigeaire 1993) indicated that in NLL this period would be an ideal time to increase CK levels in flowers.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In tobacco, TP12 is most strongly expressed just prior to, and coinciding with, full flower opening and pollen release (Drews et al 1992). The earlier study (Atkins and Pigeaire 1993) indicated that in NLL this period would be an ideal time to increase CK levels in flowers.…”
Section: Discussionmentioning
confidence: 93%
“…The rationale for this study derived from the fact that external application of CK to floral tissues of NLL at or around anthesis resulted in significantly increased pod set (Atkins and Pigeaire 1993). Because using external application of CK to the right tissue at the right time in the field is not feasible, a transgenic approach in which the phenotype would be increased CK levels in flowers at anthesis was suggested as a means to enhance pod set.…”
Section: Impact Of Transgene Expression On Development and Grain Yielmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytokinins influence a variety of developmental processes, and water stress can affect cytokinin levels in plants (Aspinall 1980;Davies et al 1986;Davies and Zhang 1991). Application of cytokinins can prevent heatinduced kernel abortion in maize and improve flower production and fruit set in other species (Carlson et al 1987;Atkins and Pigeaire 1993;Mosjidis et al 1993;Cheikh and Jones 1994). Pressurizing the roots of waterstressed wheat plants prevents browning of apical spikelets, a potential symptom of increased cytokinin level, and improves fertility (Westgate et al 1996).…”
Section: Relationship Between Tissue Water Deficit and Sterilitymentioning
confidence: 99%